Irbesartan, an angiotensin II type 1 receptor blocker, inhibits colitis-associated tumourigenesis by blocking the MCP-1/CCR2 pathway - Kensuke Hachiya (Nature Portfolio, 2021)
Abstract The introduction of anti-inflammatory therapies has enabled substantial improvement of disease activity in patients with inflammatory bowel diseases (IBD). However, IBD can lead to serious complications such as intestinal fibrosis and colorectal cancer. Therefore, novel therapies reducing the development of these complications are needed. Angiotensin II (Ang II) promotes tissue inflammation by stimulating the production of monocyte chemoattractant protein-1 (MCP-1) or proinflammatory cytokines. It plays a pivotal role in IBD progression. Although blockade of Ang II has been reported to ameliorate experimental colitis and reduce colorectal cancer risk, the cellular and molecular mechanisms remain poorly understood. Our previous work showed that irbesartan, an Ang II type 1 receptor blocker, reduced the number of C–C chemokine receptor 2-positive (CCR2+) monocytic cells in the inflamed pancreas. This study aimed to investigate the possible antifibrotic and antitumour effects of irbesartan using the azoxymethane/dextran sodium sulphate mouse model. Irbesartan suppressed MCP-1 production and the accumulation of Ly6C+CCR2+ monocytes and fibrocytes in the inflamed colon, downregulated the expression of type 1 collagen and matrix metalloproteinase 9 and inhibited the development of intestinal fibrosis and tumours. Our observations suggest that blocking the MCP-1/CCR2 pathway using irbesartan might be beneficial in preventing colitis-associated colon tumours.